2016
DOI: 10.1111/ped.13088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of bronchoscopic cryotherapy in 156 pediatric patients

Abstract: Bronchoscopic cryotherapy is effective and safe for dyspnea caused by airway obstruction, and wide application in clinic is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The use of cryotherapy through rigid bronchoscopy CRYOTHERAPY FOR TRACHEOBRONCHIAL THROMBUS for postpneumonia airway stenosis has been reported in a large series of Chinese pediatric patients (156) by Ni and colleagues. 8 This was done with good success rates and a favorable safety profile. The cryotherapeutic approach to airway stenosis involves longer treatment time and/or greater cold exposure than cryoextraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cryotherapy through rigid bronchoscopy CRYOTHERAPY FOR TRACHEOBRONCHIAL THROMBUS for postpneumonia airway stenosis has been reported in a large series of Chinese pediatric patients (156) by Ni and colleagues. 8 This was done with good success rates and a favorable safety profile. The cryotherapeutic approach to airway stenosis involves longer treatment time and/or greater cold exposure than cryoextraction.…”
Section: Discussionmentioning
confidence: 99%
“…The cryotherapeutic approach to airway stenosis involves longer treatment time and/or greater cold exposure than cryoextraction. 8 As smaller cryoprobes become available, further application of cryotherapy including cryoextraction is warranted in the pediatric population. This case supports the feasibility of using cryoextraction as a modality to recanalize the tracheobronchial tree after obstruction by a thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shu et al 12 from Shanghai Children's Hospital of Shanghai Jiao Tong University described successful alternative resections of granulation tissues during foreign body removal by flexible bronchoscopy through concomitant argon plasma coagulation application in nine children aged from 16 months to 4 years old. Ni et al 13 from Qilu Children's Hospital of Shangdong University reported bronchoscopic electrocoagulation treatment served as a safe therapeutic method in five pediatric patients of granulation tissue hyperplasia caused by foreign body in bronchus. In the present study, we showed different therapeutic modalities in granulation tissue removal from children's deep bronchi by interventional procedures via flexible bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Most strikingly, airway patency were achieved in all cases, and none of them needed further segmentectomy or lobectomy for chronic obstruction. Consistently, previous studies have discussed the successful removal of airway granulation tissues caused by foreign bodies through bronchoscopic management (e.g.,argon plasma coagulation, electrocoagulation) with an encouraging treatment efficacy 12,13. Despite different interventional strategies via bronchoscopy, these data suggest that bronchoscopic treatment modalities can provide durable successful results in pediatric patients with airway granulation tissue hyperplasia.…”
mentioning
confidence: 99%
“…However, the cryotherapy has limited freezing depth to lesion tissues, so it’s not promising for clearing large tumor tissues, and relieving airway stenosis [14, 15]. Argon plasma coagulation can damage the lesion tissues from various angles, which effectively clears the tumor tissues [16]. In the observation group, the completely effective rate and mildly effective rate were 37.21 and 11.63%, respectively, which were significantly different from those of the control group, while the partially effective rate and ineffective rate were 46.51 and 4.65%, respectively, which were not significantly different from the control group, suggesting that the argon plasma coagulation combined with cryotherapy had better treatment effect, which is consistent with previous study [17].…”
Section: Discussionmentioning
confidence: 99%